3D displacement measurement model for health monitoring of structures using a motion capture system. (January 2015) - Park, S.W.; Park, H.S.; Kim, J.H.; Adeli, Hojjat
Highlights: A method to measure 3D structural displacements using a motion capture system (MCS). The MCS can determine the movement of markers in any direction precisely. The effectiveness of the proposed model was tested using a 3-story structure. It is shown the method is accurate. Abstract: Unlike 1D or 2D displacement measurement sensors, a motion capture system (MCS) can determine the movement of markers in any direction precisely. In addition, an MCS can overcome the limitations of the sampling frequency in 3D measurements by terrestrial laser scanning (TLS) and global positioning system (GPS). This paper presents a method to measure three dimensional (3D) structural displacements using a motion capture system (MCS) with a high accuracy and sampling rate. The MCS measures 2D coordinates of a number of markers with multiple cameras; these measurements are then used to calculate the 3D coordinates of markers. Therefore, unlike previous 1D or 2D displacement measurement sensors, the MCS can determine precisely the movement of markers in any direction. In addition, since the MCS cameras can monitor several markers, measurement points are increased by the addition of more markers. The effectiveness of the proposed model was tested by comparing the displacements measured in a free vibration experiment of a 3-story structure with a height of 2.1 m using both the MCS and laser displacement sensors.